In Vitro Hydrodynamic Assessment of a New Transcatheter Heart Valve Concept (the TRISKELE) - Benyamin Rahmani; Spyros Tzamtzis; Rose Sheridan; Michael Mullen; John Yap; Alexander M. Seifalian; Gaetano Burriesci (2016)
This study presents the in vitro hydrodynamic assessment of the TRISKELE, a new system suitable for transcatheter aortic valve implantation (TAVI), aiming to mitigate the procedural challenges experienced with current technologies. The TRISKELE valve comprises three polymeric leaflet and an adaptive sealing cuff, supported by a novel fully retrievable self-expanding nitinol wire frame. Valve prototypes were manufactured in three sizes of 23, 26, and 29 mm by automated dip-coating of a biostable polymer, and tested in a hydrodynamic bench setup in mock aortic roots of 21, 23, 25, and 27 mm annulus, and compared to two reference valves suitable for equivalent implantation ranges: Edwards SAPIEN XT and Medtronic CoreValve. The TRISKELE valves demonstrated a global hydrodynamic performance comparable or superior to the controls with significant reduction in paravalvular leakage. The TRISKELE valve exhibits enhanced anchoring and improved sealing. The valve is currently under preclinical investigation.